ACTivity as medicine In Oncology for Head and Neck (ACTIOHN): a feasibility study investigating a patient-centred approach to exercise for head and neck cancer patients - Patterson, Joanne M.; Cherry, Mary G.; Levy, Andrew; Rogers, Simon N.; Brooker, Rachel C.; Bryant, Valerie M.; Lane, Steven; Nugent, Michael M.; Price, Ruth; Schache, Andrew G.; Kirton, Jennifer A.; Young, Bridget; et al. (Frontiers in Oncology, 2025)
ObjectiveTo determine the feasibility and acceptability of integrating a remote, personalised, collaborative, and flexible exercise programme into the head and neck cancer (HNC) care pathway.DesignA single arm mixed-methods feasibility study across two UK NHS hospitals.ProcedureEligible HNC patients (aged ≥ 16 years old, treated with curative intent and classified as low/medium risk according to an exercise risk stratification tool) were invited to participate between diagnosis and 8 weeks post-treatment. Patients treated with palliative intent and those identified as high risk on an exercise risk stratification tool were excluded. Following initial assessment, Cancer Exercise Specialists (CESs) and patients collaboratively devised a personalised exercise programme based on a needs analysis, preferences and goals, and informed by physical activity cancer guidelines and theory. CESs were trained in behaviour change techniques. The intervention was flexible and delivered remotely across 8 weeks, with weekly meetings and texts, and an exercise maintenance plan agreed in the final session.OutcomesEligibility, recruitment, retention and exercise adherence were primary outcomes. Quantitative outcomes included quality-of-life, fatigue and physical activity questionnaires and physical fitness tests. A qualitative sub-study explored patients’ and healthcare professionals’ (HCPs’) views on feasibility and acceptability.Results98% of patients screened were eligible; 107 patients were approached, and 76 consented (71%). Most (43%) were recruited pre-treatment. Three quarters were male and just over half had oropharyngeal cancer. Thirteen patients (17.1%) were withdrawn due to ill-health. Twenty-three (30.3%) patients dropped out, 13 after assessment but before the intervention, and ten during the intervention. Forty patients (52.6%) completed the intervention. Three quarters of exercise sessions were completed as prescribed. Patient interviews found the flexible, personalised approach valuable. Those not identifying as an ‘exerciser’ found the intervention more difficult to understand. The need for more education for both HCPs and patients regarding the benefits of exercise and its ‘fit’ within the HNC pathway was highlighted.ConclusionThis is a feasible and acceptable intervention, but some adjustments are required, to improve acceptability, recruitment processes, retention and adherence, before examining effectiveness in a definitive trial.Clinical Trial Registrationhttps://www.isrctn.com/ISRCTN82505455, identifier ISRCTN82505455.